2011
DOI: 10.1007/s00436-011-2451-z
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Ribeiroia ondatrae in the developing anuran limb disrupts retinoic acid levels

Abstract: The widespread reports of malformed frogs have sparked interest worldwide to try and determine the causes of such malformations. Ribeiroia ondatrae is a digenetic trematode, which has been implicated as one such cause, as this parasite encysts within the developing tadpole hind limb bud and inguinal region causing dramatic limb malformations. Currently, the mechanisms involved in parasite-induced limb deformities remain unclear. We sought to investigate whether the level of retinoic acid (RA), a morphogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…Therefore, the teratogenic effects appear to be taxon specific. The teratogenic factor was supposed to be retinoic acid in the trematode Ribeiroia ondatrae [48]. In the case of anomaly P, the teratogenic factor can influence the expression levels of HoxD genes [49,50] and lead to a peculiar morphology with the reduction of the hind limb's proximal parts (brachymely) and multiplication of the distal parts (polydactyly).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the teratogenic effects appear to be taxon specific. The teratogenic factor was supposed to be retinoic acid in the trematode Ribeiroia ondatrae [48]. In the case of anomaly P, the teratogenic factor can influence the expression levels of HoxD genes [49,50] and lead to a peculiar morphology with the reduction of the hind limb's proximal parts (brachymely) and multiplication of the distal parts (polydactyly).…”
Section: Discussionmentioning
confidence: 99%
“…In this host, however, all 47 specimens examined during 2014-2015 from the Lake Balaton exhibited this malformation. The cause of the bifurcation of the gill filaments caused by the Echinochasmus infection in ruffe is not known, but it may be a similar mechanism to that of R. ondatrae infection in amphibians, where Szuroczki et al (2012) have suggested that an increased level of retinoic acid might result in the malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Полиморфная природа также наблюдалась в случае аномалий Войткевича (Woitkewich 1961), деформаций у головастиков и сеголеток зеленых жаб (Henle et al 2017c,d), массовых аномалий задних конечностей, полученных в лабораторных экспериментах у шпорцевой лягушки Xenopus laevis (Коваленко [Kovalenko] 2000), а также при «аномалии P» (Rostand 1971) у зелёных лягушек рода Pelophylax, которой посвящен настоящий обзор. Механизмы индукции таких полиморфных синдромов, даже в самых изученных случаях с инвазией трематод рода Ribeiroia, до сих пор до конца непонятны и оставляют множество нерешенных вопросов (Szuroczki et al 2012).…”
Section: C Dunclassified
“…Сешен с соавторами (Session et al 1999) в этом же номере журнала "Science" показали, что дублирование конечностей под действием метацеркарий трематод было связано с механическими причинами, а не с влиянием ретиноидов. Тем не менее, спустя 12 лет было обнаружено, что концентрация различных форм ретиноевой кислоты в развивающейся аномальной конечности головастика выше на 70% по сравнению с контролем (Szuroczki et al 2012). По мере накопления новых данных было выявлено, что эта трематода вызывает деформации конечностей у порядка 60 видов амфибий как минимум в 46 штатах США (Johnson and Sutherland 2003).…”
Section: трематодная гипотеза развития аномалииunclassified